Urban Sprawl Monitoring with the help of Remote Sensing & GIS Techniques - Fatema, S; Chakrabarty, A (International Journal of Computer Sciences and Engineering, 2025)
The present study examines the use of Remote Sensing and GIS techniques in the mapping of urban sprawl (20012011) and land use/land cover change detection. The Year of 2001 and 2011 has been taken to detect the urban sprawl. An urban area is the most powerful territory on the earth. As we know in the last decade, the size of the urban areas has been continuously increased, and it will go for in the future. In the present day, urban growth is a big problem. For better livelihood, the urban areas are expanding rapidly. Remote Sensing and GIS techniques can define the process of urban sprawl. In the present study, Landsat ETM Plus satellite imageries and Google Earth Pro has been used to identify the urban sprawl of the study area